Inhibiting Integrin α5 Cytoplasmic Domain Signaling Reduces Atherosclerosis and Promotes Arteriogenesis. Issue 3 (30th January 2018) - Budatha, Madhusudhan; Zhang, Jiasheng; Zhuang, Zhen W.; Yun, Sanguk; Dahlman, James E.; Anderson, Daniel G.; Schwartz, Martin A.
Abstract : Background: Fibronectin in endothelial basement membranes promotes endothelial inflammatory activation and atherosclerosis but also promotes plaque stability and vascular remodeling. The fibronectin receptor α5 subunit is proinflammatory through binding to and activating phosphodiesterase 4D5, which inhibits anti‐inflammatory cyclic adenosine monophosphate and protein kinase A. Replacing the α5 cytoplasmic domain with that of α2 resulted in smaller atherosclerotic plaques. Here, we further assessed plaque phenotype and compensatory vascular remodeling in this model. Methods and Results: α5/2 mice in the hyperlipidemic apolipoprotein E null background had smaller plaques in the aortic root, with reduced endothelial NF‐κB activation and inflammatory gene expression, reduced leukocyte content, and much lower metalloproteinase expression. However, smooth muscle cell content, fibrous cap thickness, and fibrillar collagen were unchanged, indicating no shift toward vulnerability. In vivo knockdown of phosphodiesterase 4D5 also decreased endothelial inflammatory activation and atherosclerotic plaque size. α5/2 mice showed improved recovery from hindlimb ischemia after femoral artery ligation. Conclusions: Blocking the fibronectin‐Integrin α5 pathway reduces atherosclerotic plaque size, maintains plaque stability, and improves compensatory remodeling. This pathway is therefore a potential therapeutic target for treatment of atherosclerosis.